Glutamate and Opioid Antagonists Modulate Dopamine Levels Evoked by Innately Attractive Male Chemosignals in the Nucleus Accumbens of Female Rats - Sánchez-Catalán, María-José; Orrico, Alejandro; Hipólito, Lucía; Zornoza, Teodoro; Polache, Ana; Lanuza, Enrique; Martínez-García, Fernando; Granero, Luis; Agustín-Pavón, Carmen (Frontiers in Neuroanatomy, 2017)
Sexual chemosignals detected by vomeronasal and olfactory systems mediate intersexual attraction in rodents, and act as a natural reinforcer to them. The mesolimbic pathway processes natural rewards, and the nucleus accumbens receives olfactory information via glutamatergic projections from the amygdala. Thus, the aim of this study was to investigate the involvement of the mesolimbic pathway in the attraction towards sexual chemosignals. Our data show that female rats with no previous experience with males or their chemosignals display an innate preference for male-soiled bedding. Focal administration of the opioid antagonist β-funaltrexamine into the posterior ventral tegmental area does not affect preference for male chemosignals. Nevertheless, exposure to male-soiled bedding elicits an increase in dopamine efflux in the nucleus accumbens shell and core, measured by microdialysis. Infusion of the opioid antagonist naltrexone in the accumbens core does not significantly affect dopamine efflux during exposure to male chemosignals, although it enhances dopamine levels 40 minutes after withdrawal of the stimuli. By contrast, infusion of the glutamate antagonist kynurenic acid in the accumbens shell inhibits the release of dopamine and reduces the time that females spend investigating male-soiled bedding. These data are in agreement with previous reports in male rats showing that exposure to opposite-sex odors elicits dopamine release in the accumbens, and with data in female mice showing that the behavioral preference for male chemosignals is not affected by opioidergic antagonists. We hypothesize that glutamatergic projections from the amygdala into the accumbens might be important to modulate the neurochemical and behavioral responses elicited by sexual chemosignals in rats.